PHONOLOGICAL AWARENESS AND READING FLUENCY IN SECOND-LANGUAGE LEARNERS - Nathan Walker (International Journal of Literature and Language Studies, 2026)
This article investigates the relationship between phonological awareness and reading fluency among second-language learners. The study responds to the problem that second-language readers may recognize vocabulary visually but still struggle with fluent decoding when phonological processing is weak. Using correlational classroom study complemented by qualitative error analysis, the article analyzes phoneme segmentation tasks, oral reading samples, and teacher observation notes from intermediate English learners. The findings indicate that learners with stronger phonological awareness read more accurately and with better pacing; common errors involved consonant clusters, vowel length, and stress placement. The article argues that reading instruction for language learners should integrate meaning-based reading with explicit attention to sound-symbol relationships. By connecting language, literary form, and interpretation, the study offers a concise contribution to current debates in literature and language studies.